2018
DOI: 10.1038/s41598-018-30336-6
|View full text |Cite
|
Sign up to set email alerts
|

Textural features of cervical cancers on FDG-PET/CT associate with survival and local relapse in patients treated with definitive chemoradiotherapy

Abstract: We retrospectively reviewed the records of 142 patients with stage IB–IIIB cervical cancer who underwent 18F-FDG-PET/CT before external beam radiotherapy plus intracavitary brachytherapy and concurrent chemotherapy. The patients were divided into training and validation cohorts to confirm the reliability of predictors for recurrence. Kaplan–Meier analysis was performed and a Cox regression model was used to examine the effects of variables on overall survival (OS), progression-free survival (PFS), distant meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 40 publications
3
29
0
Order By: Relevance
“…In each CT or SUV image, the intensity was first normalized into 64 gray levels. The texture features were computed based on the gray level co-occurrence matrix (GLCM) (1618) and gray level run-length matrix (GLRM) (18, 19).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In each CT or SUV image, the intensity was first normalized into 64 gray levels. The texture features were computed based on the gray level co-occurrence matrix (GLCM) (1618) and gray level run-length matrix (GLRM) (18, 19).…”
Section: Methodsmentioning
confidence: 99%
“…An element of a GLCM measures the number of two specified gray levels separated by a given distance in a specified direction (1618). After the construction of the GLCM, the following eight frequently used features were computed (1618): Energy, entropy, correlation, inverse difference moment, inertia, cluster shade, cluster prominence, Haralick correlation. Each GLCM feature was computed in 13 directions (in 3D) with a distance of one voxel between the pair of voxels.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the PET prognostic studies for cervix cancer are qualitative correlative studies 36 - 38 or have focused on single quantitative measures like textural analysis. 39 Using a cohort of 14 cervical cancer patients treated at a single institution, El Naqa et al found that a combination of intensity-volume histogram (IVH) metrics and texture features extracted from PET images had high predictive power for response to treatment. 11 The models in our study were constructed using a larger dataset consisting of 75 patients for model training and testing.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment was described previously [18,21]. All patients were treated with intensity-modulated radiotherapy.…”
Section: Treatmentmentioning
confidence: 99%